2012
DOI: 10.4028/www.scientific.net/jnanor.18-19.257
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of GdVO<sub>4</sub>:Eu<sup>3+</sup>, Al <sup>3+</sup> Phosphors under VUV Excitation

Abstract: The microstructure and photoluminescence properties of Gd0.94-xAlxEu0.06VO4 (0≤x≤0.04) phosphors with various Al3+ contents were investigated. The phosphors showed a nanocrystalline nature and a high-quality powder characteristic. The crystallite sizes of the phosphors were calculated to be 46-48 nm. The annealed Gd0.94-xAlxEu0.06VO4 phosphors crystallized in the tetragonal structure. In the emission spectra, several emission peaks were observed over the measured wavelength range (500-750 nm), which were cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the other hand, rare earth vanadates have been studied extensively in the last decade, and they are of great interest as hosts for luminescence materials (6)(7)(8). The properties of nanostructure are highly structure-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, rare earth vanadates have been studied extensively in the last decade, and they are of great interest as hosts for luminescence materials (6)(7)(8). The properties of nanostructure are highly structure-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches showed that impurity ions could produce a change of symmetry and vibration modes around the luminescence center to result in the enhancement of the luminescence intensity [7][8][9] . Therefore, in this paper, Sr2CeO4 and impurity ions doped Sr2CeO4:M (M = Mg, Ca, Zn, Al) phosphors were synthesized by hydrothermal method using (NH4)2CO3 as the precipitation agent.…”
mentioning
confidence: 99%